Cycling related major trauma in Ireland. Issue 5 (May 2020) - Foley, James; Cronin, Marina; Brent, Louise; Lawrence, Tom; Simms, Ciaran; Gildea, Kevin; Ryan, John; Deasy, Conor; Cronin, John
Highlights: Cycling injuries occur in a predominantly young male population and are associated with more severe injuries than the overall trauma population. A common mechanism for cycling injuries is a collision with a motor vehicle, but the mechanism of injury is unknown for the majority of collisions. Using hospital data provides valuable information on the injuries sustained by cyclists, and could be used to guide injury prevention strategies. Abstract: Introduction: Cycling as a means of transport or recreational activity is increasing in popularity in Ireland. However, increasing numbers of cyclists may lead to an increased number of bicycle collisions and fatalities. The Road Safety Authority is the statutory body for road safety in Ireland but uses police data alone to collate cycling collision statistics. This may lead to an underestimation of cycling injuries in Ireland. Using hospital statistics may provide a greater understanding of cycling trauma in Ireland. Objective: The present study examines cycling related trauma in Ireland using the Major Trauma Audit (MTA) data collected via the Trauma and Research Network (TARN) from hospitals in Ireland for the period 2014 to 2016. The database was interrogated for demographics, mechanism of injury, injury characteristics and patient outcomes. Results: There were 410 cycling collisions recorded in the TARN database which represented 4.4% of trauma captured by TARN for the study period. Of this cohort 79% were male compared with 58% in the overall (TARN) trauma cohort ( p  < 0.001) and the median (IQR) age was 43.8 years (31.0, 55.7) which is younger than the median (IQR) of 58.9 (36.2, 76.0) years for the overall trauma cohort ( p  < 0.001). Cycling collisions had a median (IQR) injury severity score (ISS) of 10 (9, 20) which was higher than the overall trauma cohort ISS of 9 (9, 17). Of the mechanisms observed for cycling trauma, 31.7% ( n  = 130) had a collision with a motor vehicle. Of those who did not wear a helmet, 52.2% ( n  = 47) sustained a head injury compared with 27.5% ( n  = 44) in the group who were wearing a helmet ( p  < 0.001). Conclusion: The TARN data presented in this paper builds a more complete overview of the burden of cycling collisions in Ireland. Particular points of focus are that serious cycling injuries occur in a predominantly male population, and that only around 30% of cases are recorded as involving a motor vehicle, with the majority having an unknown mechanism of injury. There was an association between helmets and head injuries in this study, but there are likely other contributing factors such as mechanism of injury, velocity or cycling infrastructure. Using hospital data such as the MTA provides valuable information on the injuries sustained by cyclists, but more prospective studies to capture injury mechanism and contributing factors are needed.